2018
DOI: 10.3390/ijerph15050935
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Emerging Contaminants and Estrogenic Activity from Wastewater Treatment Plant Effluent with UV/Chlorine and UV/H2O2 Advanced Oxidation Treatment at Pilot Scale

Abstract: Effluent of a municipal wastewater treatment plant (WWTP) was treated on-site with the UV/chlorine (UV/HOCl) advanced oxidation process (AOP) using a pilot plant equipped with a medium pressure UV lamp with an adjustable performance of up to 1 kW. Results obtained from parallel experiments with the same pilot plant, where the state of the art UV/H2O2 AOP was applied, were compared regarding the removal of emerging contaminants (EC) and the formation of adsorbable organohalogens (AOX). Furthermore, the total es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…WWTP effluent MP-UV/chlorine >97% removal at chlorine dose >5 mg/L [48] improve the toxicity of treated water. Thus, optimization of the operational condition is important for toxicity control by UV/chlorine AOPs.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…WWTP effluent MP-UV/chlorine >97% removal at chlorine dose >5 mg/L [48] improve the toxicity of treated water. Thus, optimization of the operational condition is important for toxicity control by UV/chlorine AOPs.…”
Section: Toxicitymentioning
confidence: 99%
“…The reported contact time of UV irradiation was widely varied from 6 s to 420 min. However, 6-40 s of contact time was applied in the full and pilot scale experiments [47,48,129]. Since the chlorine dose was relatively low, namely ≤10 mg-Cl 2 /L, a short contact time less than 1 min may be enough for UV/ chlorine AOPs.…”
Section: Applicationsmentioning
confidence: 99%
“…In a study with real effluent of a WWTP (continuous operation with 1 m 3 /h, medium pressure UV lamp operated at 0.4–1.0 kW) by Rott et al [ 7 ] it was shown at pilot scale that the UV/chlorine AOP is superior to the UV/H 2 O 2 AOP [ 8 ] in terms of the elimination of ECs, the bacterial count and the total estrogenic activity, as much lower mass concentrations of oxidant are required. All investigations in this study were carried out at NH 4 + -N concentrations <0.1 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…A major concern associated with the UV/chlorine AOP is the formation of potentially toxic and lipophilic halogenated degradation by-products such as adsorbable organohalogens (AOX) [ 7 , 9 , 10 ]. Side reactions contribute to the fact that the dosed chlorine immediately reacts to form combined chlorine (CC) or decomposes into chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The UV/H 2 O 2 system is a type of AOP, in which hydrogen peroxide (H 2 O 2 ) is added in the presence of UV light to generate hydroxyl radicals [16][17][18]. It is found that the UV/H 2 O 2 process can remove a large range of organic pollutants, including cyanobacterial toxins [19], diclofenac [20], amoxicillin [21], and other emerging contaminants [22][23][24].Benzophenone-type UV filters are usually the hardly biodegradable substances [25]. There are over 20 benzophenone-type UV filters, including HBP, BP, benzophenone-2, benzophenone-3 (BP3), benzophenone-4, benzophenone-5, and benzophenone-9.…”
mentioning
confidence: 99%